Merubah, Merobah atau Mengubah? Analisa terhadap Variasi Bentuk Awalan dalam Proses Morfologis Pembentukan Kata Bahasa Indonesia - Maulida, Siti Zumrotul (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2015)
Among the seven prefixes in Indonesian, meN- is the most productive one. It is a fact that many users of Indonesian still incorrectly apply such prefix. Pre meN- is used to make verb. Morphologically, prefix meN- is combined with basic word. However, sometimes the morphological process is misunderstood, so the derived word is incorrect.